Macro-anatomical and osteometric investigations on apparatus hyobranchialis in quails - Ozkan, ZE (Indian Veterinary Journal, 2004)
The quails (Coturniz coturnix) are flying and running birds and belong to the Phasianidae family order Galliformes (Austin et al., 1975; Demirsoy, 1998). There are some anatomical studies on apparatus hyobranchialis in domestic fowls (Mc Leiland, 1968; Zweers, 1974; Homberger and Meyers, 1989; Tasbas et al., 1989) and in some exotic avians such as parrots and budgerigars (Ozkan, 2002; Ozkan, 2003) but macro-anatomical featues on apparatus hyobranchialis in quails have not been investigated in detail. The aim of this study is to investigate the gross anatomical and osteometric features of apparatus hyobranchialis in male and female quails.
Keywords: Gallus-Gallus